Exploring nature’s antidote: unveiling the inhibitory potential of selected medicinal plants from Kisumu, Kenya against venom from some snakes of medical significance in sub-Saharan Africa - Okumu, Mitchel; Mbaria, James; Gikunju, Joseph; Mbuthia, Paul; Madadi, Vincent; Ochola, Francis (Frontiers in Pharmacology, 2024)
Background: The present study investigated the efficacy of Conyza bonariensis, Commiphora africana, Senna obtusifolia, Warburgia ugandensis, Vernonia glabra, and Zanthoxylum usambarense against Bitis arietans venom (BAV), Naja ashei venom (NAV), and Naja subfulva venom (NSV).Methods: 40 extracts and fractions were prepared using n-hexane, dichloromethane, ethyl acetate, and methanol. In vitro efficacy against snake venom phospholipase A2 (svPLA2) was determined in 96-well microtiter and agarose-egg yolk coagulation assays. in vivo efficacy against venom-induced cytotoxicity was determined using Artemia salina. Two commercial antivenoms were used for comparison.: The 96-well microtiter assay revealed poor svPLA2 inhibition of BAV by antivenom (range: 20.76 ± 13.29 % to 51.29 ± 3.26%) but strong inhibition by dichloromethane and hexane fractions of C. africana, hexane and ethyl acetate extracts and fraction of W. ugandensis, dichloromethane fraction of V. glabra, and the methanol extract of S. obtusifolia. The methanol extract and fraction of C. africana, and the hexane extract of Z. usambarense strongly inhibited svPLA2 activity in NAV. The hexane and ethyl acetate fractions of V. glabra and the dichloromethane, ethyl acetate, and methanol extracts of C. africana strongly inhibited svPLA2 in NSV. The agarose egg yolk coagulation assay showed significant inhibition of BAV by the dichloromethane fraction of C. africana (EC50=3.51±2.58 µg/ml), significant inhibition of NAV by the methanol fraction of C. africana (EC50=7.35±1.800 µg/ml), and significant inhibition of NSV by the hexane extract of V. glabra (EC50=7.94±1.50 µg/ml). All antivenoms were noncytotoxic in A. salina but the methanol extract of C. africana and the hexane extracts of V. glabra and Z. usambarense were cytotoxic. The dichloromethane fraction of C. africana significantly neutralized BAV-induced cytotoxicity, the methanol fraction and extract of C. africana neutralized NAV-induced cytotoxicity, while the ethyl acetate extract of V. glabra significantly neutralized NSV-induced cytotoxicity. Glycosides, flavonoids, phenolics, and tannins were identified in the non-cytotoxic extracts/fractions. Conclusions: These findings validate the local use of C. africana and V. glabra in snakebite but not C. bonariensis, S. obtusifolia, W. ugandensis, and Z. usambarense. Further work is needed to isolate pure compounds from the effective plants and identify their mechanisms of action.